Large-scale production and evaluation of marker-free indica rice IR64 expressing phytoferritin genes - Oliva, Norman; Chadha-Mohanty, Prabhjit; Poletti, Susanna; Abrigo, Editha; Atienza, Genelou; Torrizo, Lina; Garcia, Ruby; Dueñas, Conrado; Poncio, Mar Aristeo; Balindong, Jeanette; Manzanilla, Marina; Montecillo, Florencia; et al. (Springer, 2014)
Biofortification of rice (Oryza sativa L.) using a transgenic approach to increase the amount of iron in the grain is proposed as a low-cost, reliable, and sustainable solution to help developing countries combat anemia. In this study, we generated and evaluated a large number of rice or soybean ferritin over-accumulators in rice mega-variety IR64, including marker-free events, by introducing soybean or rice ferritin genes into the endosperm for product development. Accumulation of the protein was confirmed by ELISA, in situ immunological detection, and Western blotting. As much as a 37- and 19-fold increase in the expression of ferritin gene in single and co-transformed plants, respectively, and a 3.4-fold increase in Fe content in the grain over the IR64 wild type was achieved using this approach. Agronomic characteristics of a total of 1,860 progenies from 58 IR64 single independent transgenic events and 768 progenies from 27 marker-free transgenic events were evaluated and most trait characteristics did not show a penalty. Grain quality evaluation of high-Fe IR64 transgenic events showed quality similar to that of the wild-type IR64. To understand the effect of transgenes on iron homeostasis, transcript analysis was conducted on a subset of genes involved in iron uptake and loading. Gene expression of the exogenous ferritin gene in grain correlates with protein accumulation and iron concentration. The expression of NAS2 and NAS3 metal transporters increased during the grain milky stage.